Age–period–cohort effects of adult cigarette smoking in the United States, 1971–2020 - Dinko Kranjac; Ashley W. Kranjac (Scientific Reports)
Abstract The rates of cigarette use among American adults have dropped substantially throughout the last six decades, yet smoking remains the leading cause of preventable disease and death in the United States. It is crucial to identify the putative time-varying population-level factors of age, period, and cohort that influenced the decrease in smoking prevalence so we can maintain the downward trend. We used 49 years of data from the National Health and Nutrition Examination Survey (NHANES) and hierarchical age–period–cohort (HAPC) analysis to examine lifecycle, historical, and generational distribution of smoking among Americans aged 18–74 years old. The prevalence of smoking has declined tremendously from 1971 to 2020 because American adults over the age of ~ 27 had a lower probability of cigarette use, but the rates of decrease have been unequal among birth cohorts. We uncovered the putative temporal contributors to population-level decreases in the prevalence of current smoking among American adults over the last nearly fifty years. Policy-makers ought to prioritize tobacco control efforts that focus on young adults, and should address the cohort-specific challenges in order to maintain the downward trend in smoking prevalence and further reduce the number of preventable premature deaths due to cigarette use.